1970
DOI: 10.1071/zo9700295
|View full text |Cite
|
Sign up to set email alerts
|

Diapause in the aestivating egg of Halotydeus destructor (Acari : Eupodidae)

Abstract: The occurrence of an aestivating diapause in the eggs of the red-legged earth mite, H. destructor, is established. The production of diapause eggs in females is influenced by the increasing maturity of food plants in the spring. Morphogenesis is resumed following exposure to early summer conditions for 4-6 weeks in the field. In the laboratory, diapause development was achieved by exposing the eggs to various combinations of temperature and relative humidity. The most effective treatment was exposure for 32 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
4

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 8 publications
1
48
0
4
Order By: Relevance
“…The constant rate of development of the mites throughout the summer rearing period indicated that diapause eggs were not developed. Mites were transferred off plants before they started to flower, because flowering may trigger the production of diapause eggs (Wallace, 1970a). The temperature was not expected to influence H. destructor survival over the range used here.…”
Section: Discussionmentioning
confidence: 99%
“…The constant rate of development of the mites throughout the summer rearing period indicated that diapause eggs were not developed. Mites were transferred off plants before they started to flower, because flowering may trigger the production of diapause eggs (Wallace, 1970a). The temperature was not expected to influence H. destructor survival over the range used here.…”
Section: Discussionmentioning
confidence: 99%
“…Its induction, maintenance and ending is mediated by biotic and abiotic factors, such as temperature (Masaki & Sakai 1965, Sullivan & Wallace 1968; photoperiod (Masaki 1958, Sullivan & Wallace, 1965; humidity (Tauber & Tauber 1976); food quality and availability (Wallace 1970); host physiological status and population density (Chapman et al 1955, Stewart et al 1967 and intraspecific variation (Matsumoto et al 1951e 1952, Poitout & Bues 1977.…”
Section: Resultsmentioning
confidence: 99%
“…It can be a primary diapause regulating factor or can play role in interaction with temperature and photoperiod. In two Australian species, a collembola (Sminthurus virdis), and a mite (Halotydeus destructor), the aestival diapause is influenced by food quality where maturity of host plant induces diapause [50]. In addition to aestivation, hibernating insects may also be influenced by food.…”
Section: Foodmentioning
confidence: 99%